2016
DOI: 10.1002/app.43703
|View full text |Cite
|
Sign up to set email alerts
|

Properties and preparation of olefin block copolymer/thermoplastic polyurethane blends

Abstract: The properties of olefin block copolymer (OBC)/thermoplastic polyurethane (TPU) blends with or without maleic anhydride (MA) modification were characterized and compared. Compared with the OBC/TPU blends, OBC-g-MA/TPU blends displayed finer morphology and reduced domain size in the dispersed phase. The crystallization temperatures of TPU decreased significantly from 155.9 8C (OBC/TPU) to 117.5 8C (OBC-g-MA/TPU) at low TPU composition in the blends, indicating the inhibition of crystallization through the suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In these studies, TPUs were blended with olefin block copolymer (OBC), polyolefin elastomer (POE), polyamide elastomer (PAE), maleic anhydride-grafted styrene-ethylenebutylene-styrene (SEBS-g-MA), and poly(ε-caprolactone) (PCL). [16][17][18][19][20] Chen et al investigated thermal and mechanical properties of OBC/TPU blends with or without maleic anhydride (MA) modification. 16 They found that OBC-g-MA/TPU blends displayed finer morphology and higher thermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, TPUs were blended with olefin block copolymer (OBC), polyolefin elastomer (POE), polyamide elastomer (PAE), maleic anhydride-grafted styrene-ethylenebutylene-styrene (SEBS-g-MA), and poly(ε-caprolactone) (PCL). [16][17][18][19][20] Chen et al investigated thermal and mechanical properties of OBC/TPU blends with or without maleic anhydride (MA) modification. 16 They found that OBC-g-MA/TPU blends displayed finer morphology and higher thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Chen et al investigated thermal and mechanical properties of OBC/TPU blends with or without maleic anhydride (MA) modification. 16 They found that OBC-g-MA/TPU blends displayed finer morphology and higher thermal stability. They also reported a considerable improvement in the mechanical properties of OBC-g-MA/TPU blends such as tensile strength and Young's modulus compared to OBC/TPU blends.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] PU also exhibits a number of desirable properties, including good acoustic properties, oil resistance, aging resistance, adhesion, and wear resistance. Moreover, the length of the main chain, the number of branches, and the degree of crosslinking can be controlled by changing the ratio of soft and hard segments, grafting, copolymerization, and so on; this changes the microstructure of PU.…”
Section: Introductionmentioning
confidence: 99%
“…Block copolymers are promising to solve above problems because of a well‐defined molecular structure . Many studies have shown that the mechanical and rheological properties of various blends are remarkably improved by adopting block copolymers . Similar to anionic polymerization, controlled/living radical polymerization (CLRP) is a powerful tool to synthesize complex polymers like block copolymers and gradient copolymers, especially suitable for polar monomers .…”
Section: Introductionmentioning
confidence: 99%